Factors that affect the English language teaching - learning process in Ecuadorian public high schools, estudio realizado en 5 colegios públicos de la ciudad de Cuenca, provincia del Azuay, en el período Abril - Agosto 2012 - Castillo Sarango, Soledad Monserrath (2013)
This research is focused on the factors that affect the English language teaching -learning process in Ecuadorian public high schools; its main purpose is to analyze the factors that affect the teaching -learning process. This research was carried out in five public high schools where English as a second language is taught. The participants were 15 English teachers and 15 students. Three teachers and three students were selected per high school. This research was based on 15 teachers´ questionnaires, 15 teachers´ interviews, 15 students´ questionnaires, and 15 observation sheets, whose results were registered in predesigned formats. The quantitative analysis was focused on the frequency and tabulation of the results obtained from the 20 questions of the teachers´ questionnaires, the observations done in every class, and the interviews made to each one of the teachers and students. Factors such as teaching techniques, lesson design, number of students, classroom space, teaching resources, and even institution monitoring are the most important aspects that affect the English teaching-learning process.